The impact of the 30 most cited articles on hip arthroscopy: what is the subject matter?. Issue 1 (24th February 2020) - von Glinski, Alexander; Yilmaz, Emre; Goodmanson, Ryan; Pierre, Clifford; Frieler, Sven; Shaffer, Andre; Ishak, Basem; Lee, Cara Beth; Mayo, Keith
Abstract: The purpose of this study was to identify the 30 most cited articles on hip arthroscopy and discuss their influence on recent surgical treatment. Due to advancements in hip arthroscopy, there is a widening spectrum of diagnostic and treatment indications. The purpose of this study was to identify the 30 most cited articles on hip arthroscopy and discuss their influence on contemporary surgical treatment. The Thomson Reuters Web of Science was used to identify the 30 most cited studies on hip arthroscopy between 1900 and 2018. These 30 articles generated 6152 citations with an average of 205.07 citations per item. Number of citations ranged from 146 to 461. Twenty-five out of the 30 papers were clinical cohort studies with a level of evidence between III and IV, encompassing 4348 patients. Four studies were reviewed (one including a technical note) and one a case report. We were able to identify the 30 most cited articles in the field of hip arthroscopy. Most articles were reported in high-impact journals, but reported small sample sizes in a retrospective setting. Prospective multi-arm cohort trials or randomized clinical trials represent opportunities for future studies.